Innovative Crumple-Sheet Biobr/G-C3n4 Heterostructures for Enriched Photocatalytic Degradation of Tetracycline Hydrochloride - Radhalayam, D (Elsevier Ltd, 2026)
The removal of persistent antibiotics from water remains a critical environmental challenge. In this work, BiOBr, g-C3N4, and BiOBr/g-C3N4 heterostructures with ratios of 1:1, 2:1, and 3:1 was synthesized and characterized using X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), UV–visible spectroscopy, and X-ray photoelectron spectroscope (XPS). XRD confirmed tetragonal heterostructures, while SEM and TEM revealed a crumple-sheet morphology that enhances surface area and active sites. UV–visible analysis indicated suitable band gaps for visible-light absorption. Photocatalytic degradation of tetracycline hydrochloride demonstrated that BiOBr/g-C3N4–2:1 achieved 99.1 % efficiency, outperforming pure BiOBr (65.4 %) and g-C3N4 (43.8 %). This superior activity is attributed to synergistic interactions between BiOBr and g-C3N4, improved charge separation, rapid electron–hole transfer, and generation of reactive species (·OH, ·O2−), combined with the crumpled morphology that promotes light harvesting and pollutant adsorption. These results highlight the novelty and effectiveness of crumple-sheet BiOBr/g-C3N4 heterostructures as eco-friendly, efficient, and reusable photocatalysts for antibiotic-contaminated water treatment. © 2025 Elsevier Ltd